2017
DOI: 10.3233/rnn-160692
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine increases the rate of motoneuron death following peripheral nerve injury

Abstract: Our data suggest that bupivacaine exacerbates levels of cell death in injured motoneurons. It has been proposed that once a nerve is damaged, it becomes more susceptible to injury elsewhere along the nerve. Thus, an improved understanding of the effects of local anesthetics on neuron survival and axon regeneration may lead to strategies to identify patients at higher risk for permanent neural deficits after peripheral nerve blocks and/or decrease the risk of neural deficit following peripheral nerve blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The short and intermediate acting local anesthetics (lidocaine, 2, 3-chloroprocaine, mepivacaine) did not exacerbate FMN death nor delay functional recovery in any injury model when applied immediately or delayed. Of note, our prior publication reports FMN survival of 35% after facial nerve transection and immediate treatment with bupivacaine, while the present study reports FMN survival of 63% (Byram et al, 2017). There are two major differences between these studies: 1) Our prior study used a much higher concentration of bupivacaine (0.75%) compared to the present study (0.25%) and 2) our prior study did not use Gelfoam for application.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…The short and intermediate acting local anesthetics (lidocaine, 2, 3-chloroprocaine, mepivacaine) did not exacerbate FMN death nor delay functional recovery in any injury model when applied immediately or delayed. Of note, our prior publication reports FMN survival of 35% after facial nerve transection and immediate treatment with bupivacaine, while the present study reports FMN survival of 63% (Byram et al, 2017). There are two major differences between these studies: 1) Our prior study used a much higher concentration of bupivacaine (0.75%) compared to the present study (0.25%) and 2) our prior study did not use Gelfoam for application.…”
Section: Discussionsupporting
confidence: 42%
“…Our present data demonstrate differential toxicity between local anesthetics on an injured nerve despite a common mechanism of action between all local anesthetics. In a previously published study, we demonstrated that bupivacaine, but not lidocaine, exacerbated FMN death after a facial nerve transection (Byram et al, 2017). Others have also demonstrated the neurotoxicity of bupivacaine in vitro (Lirk et al, 2008;Werdehausen et al, 2009;Yamashita et al, 2003;Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…For instance, bupivacaine, an amide‐type local anesthetic, is commonly used for pain management, epidural or spinal anesthesia, and nerve blockade in clinical patients . However, accumulating evidence suggests that local anesthetics can induce toxicity to various tissues including nerve and cause postoperative neurological complications such as cauda equina syndrome, sensory disturbance, and motor paralysis, which strikingly limits their efficacy . For example, bupivacaine exposure resulted in the reduction of cell viability and the increase of lactate dehydrogenase release, apoptotic rate and cleaved caspase‐3 level in SH‐SY5Y cells .…”
Section: Introductionmentioning
confidence: 99%